Design Of Key Performance Indicator On Lawet Coffee - Stellin Stellin; Evi Silvana Muchsinati (Universitas Internasional Batam, 2023)
Lawet Coffee is a business that engaged in the field of culinary that mainly focus on coffee which located in Nusantara Street, Tanjung Balai Karimun. This Lawet Coffee business is included as Small and Medium Enterprise (SME) that gives satisfaction and sustain the customers loyalties. However, this business has a problem regarding the performance evaluation of the employees, which could cause the business does not able to reach the target of sales and could end up the business need to be shut down forcefully. A method for evaluate the employees performances are necessarily needed, it will be effective and efficient by using a method called Balance Score Card which part of Key Performance Indicator. Result and surface is an internal and external of SWOT analysist method, result of mapping strategy and combination of the SWOT analysist results are a formation of KPI. Business partner is having changes regarding the KPI formula which necessarily created for helping the partner of the business in evaluating from internal side as well as external side. Suggestion for the next study or research, expected to be able to design long time period and short time period of sales targets in order to expand the partner business quality with the new innovation.